Youth Graduates Employment Country Studies of Albania and North Macedonia in Economics Programs (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Albania and North Macedonia, as many countries in South-Eastern Europe, struggle with youth unemployment which is persistent, acute and unresponsive to the education of young people in both countries. High school graduates often decide to continue university education for better job perspectives and advancement. High education is often perceived as a guarantee for employment. But statistics show that youth employment faces many challenges and has higher rates compared to other categories of the population. Therefore it is the aim of this study to address a general panorama of the graduated youth employment and unemployment through two case studies: Luigj Gurakuqi (LG) the University of Shkodra in Albania and South-East European (SEE) University in North Macedonia. A framework of comparative analysis with focus investigation of the employability of youth in Albania and North Macedonia is presented. Special attention is given to the economics cohorts of students graduated in the last decade. Questionnaires are delivered to this category of graduated students of two universities. Qualitative and quantitative analyses are presented giving an overall view with the specifics of each university. A statistical technique as logistic regression analysis is used to estimate the correlation between employment/unemployment and the various explanatory variables. Regression analyses of the graduated student’s questionnaires of the LG University in Albania and SEE University in North Macedonia show that the GPA of the bachelor program plays an important role in being employed. While only LG University questionnaires results show relationship of variables as gender, time of graduation, and master education level to the employment status of the graduates students.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.